Effect of Kapok and Oil Polypropylene - MOHD BASIR, NUR HASANAH BINTI MOHD BASIR; Yunos, Muhamad Zaini (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Non-abrasive, lightweight, controllable, non-toxic, affordable, biodegradable natural fibers. Natural fibers are less helpful since they are hydrophobic and absorb water poorly. This research seeks to establish the mechanical and physical properties of kapok- and oil-reinforced polypropylene composites. Determine the composite’s strength and weight. 0%, 5%, 7%, and 10% kapok and oil are mixed with polypropylene resins and pulverized. Injection molding creates a tensile and impact pattern from the pellet. Tensile, impact, density, thermal, and SEM testing are then performed. This test shows that fiber modification improves the composite’s physical attributes, but it has low tensile and impact strength. Tests include tensile, impact, density, heat, and SEM. This experiment shows that fiber modification enhances the composite’s physical attributes, yet testing indicated low tensile and impact strength.